1974
DOI: 10.1111/j.1471-4159.1974.tb10754.x
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐aminolevulinic Acid Uptake by Rabbit Brain Cerebral Cortex

Abstract: Abstract— δ‐Aminolevulinic acid (δ‐ALA) was taken up by rabbit brain cortical slices to a concentration greater than that in the surrounding medium. The process responsible for this accumulation of δ‐ALA shows many of the properties characteristic of an active transport system. δ‐ALA is taken up by a system which exhibits some allosteric kinetic properties, and is specific to a relatively high degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…In this context however it is noteworthy that Becker et al reported that brain tissue preparations could concentrate ALA when added to the surrounding medium. 29 The Valsalva manoeuvre has been previously reported to be a good indicator of parasympathetic dysfunction in diabetic patients, and in this study was found to be abnormal in latent acute intermittent porphyria. This observation is in keeping with the subclinical sensorimotor neuropathy often present in these latent acute intermittent porphyria cases as detected by nerve conduction studies.30 Yet the Valsalva manoeuvre remained normal in the acute intermittent porphyria patients in remission whereas heart-rate variation during deep breathing was significantly reduced.…”
Section: Discussionsupporting
confidence: 56%
“…In this context however it is noteworthy that Becker et al reported that brain tissue preparations could concentrate ALA when added to the surrounding medium. 29 The Valsalva manoeuvre has been previously reported to be a good indicator of parasympathetic dysfunction in diabetic patients, and in this study was found to be abnormal in latent acute intermittent porphyria. This observation is in keeping with the subclinical sensorimotor neuropathy often present in these latent acute intermittent porphyria cases as detected by nerve conduction studies.30 Yet the Valsalva manoeuvre remained normal in the acute intermittent porphyria patients in remission whereas heart-rate variation during deep breathing was significantly reduced.…”
Section: Discussionsupporting
confidence: 56%
“…Other forms of experimentation (e.g., PEPT2 knockout mice) are needed to verify whether there are indeed two transporters. Previous studies on other tissues have suggested that 5‐ALA interacts with GABA, glutamate, and PAH transporters (McGeer et al, 1961 ; Becker et al, 1974 ; McLoughlin and Cantrill, 1984 ; Cheeks and Wedeen, 1986 ; Garcia et al, 1998). Evidence (effects of Na + removal or ouabain) indicates that there are Na + ‐dependent transporters for these three compounds at the choroid plexus (Holloway and Cassin, 1972 ; Kim et al, 1996 ; Ramanathan et al, 1997 ; J. Xiang and R. F. Keep, unpublished observations on glutamate and PAH).…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism(s) involved in choroid plexus transport have not been examined. In a number of other tissues, 5‐ALA uptake has been shown to be energy dependent, and there is evidence that 5‐ALA can interact with a number of transport systems, including those for GABA (McGeer et al, 1961 ; Becker et al, 1974 ; Garcia et al, 1998), glutamate (McLoughlin and Cantrill, 1984), p ‐aminohippurate (PAH) (Cheeks and Wedeen, 1986), and the di‐/tripeptide transporters PEPT1 and PEPT2 (Doring et al, 1998), although for glutamate there is question over whether 5‐ALA is merely an inhibitor rather than a substrate for the transporter (Brennan and Cantrill, 1979).…”
mentioning
confidence: 99%
“…[4-I4C]ALA has previously been shown to be taken up into rabbit brain slices by a process which is temperature-and Na+ -dependent and inhibited by 2,4-dinitrophenol (Becker et al, 1974). But, in addition, ALA uptake into brain slices was found to be saturable and significantly inhibited by ouabain and KCN, which suggested that it involved an active transport system (Becker et al, 1974). The discrepancy may be attributed to the fact that cells in culturr, are less differentiated than in the adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of [4J4C]ALA by the cultures was not estimated and, although Becker et al (1974) demonstrated that rabbit cortex slices did not metabolise [14C]ALA, the possibility that the less differentiated cells in culture metabolise [14C]ALA cannot be excluded. [4-14C]ALA uptake into neurons and glia was linear for 20 min (Fig.…”
Section: Ala Uptake Into Neurons and Gliamentioning
confidence: 99%